Integrating Creative and Narrative-Based Art Practices Into Holistic Health, Wellness, and Therapeutic Care Programs Worldwide - Akintayo Ezekiel Akintobi (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Integrating creative and narrative-based art practices into holistic health, wellness, and therapeutic care programs has emerged as a dynamic and evidence-supported approach to enhancing patient outcomes, fostering resilience, and promoting overall well-being. This study examines the transformative potential of embedding visual arts, music, dance, drama, storytelling, and other narrative-driven modalities within diverse healthcare and wellness contexts worldwide. Drawing on interdisciplinary insights from psychology, art therapy, medical humanities, and public health, it explores how these practices address the physical, emotional, cognitive, and social dimensions of care. Creative and narrative-based interventions are shown to empower patients by validating personal experiences, enhancing self-expression, and reducing stigma, particularly in mental health care, palliative care, and rehabilitation settings. Globally, these approaches have been successfully incorporated into hospitals, community clinics, wellness retreats, and post-trauma recovery programs, demonstrating measurable benefits such as improved stress regulation, pain management, emotional resilience, and interpersonal communication. The study highlights case examples where collaborative partnerships between healthcare providers, artists, and community stakeholders have resulted in culturally sensitive and contextually relevant programs that respect diverse traditions while embracing innovation. Furthermore, it discusses the role of narrative frameworks in fostering meaning-making, strengthening identity, and promoting patient-centered care that transcends purely biomedical models. Attention is given to how creative arts can bridge cultural gaps, encourage inclusivity, and stimulate empathy among practitioners and patients alike. The analysis also considers implementation challenges, including resource allocation, training, and institutional acceptance, while offering strategies for sustainable integration into mainstream health systems. By situating creative and narrative-based art practices within holistic care paradigms, this research underscores their capacity to enrich treatment experiences, support preventive health initiatives, and contribute to global wellness strategies. Ultimately, the study affirms that art, when strategically integrated into therapeutic programs, is not only an aesthetic or recreational activity but a vital, evidence-informed component of comprehensive health and wellness care worldwide.